No longer ‘publishing as usual' - Bocock, Piers (Technical Centre for Agricultural and Rural Cooperation, 2013)
Despite the spread in the use of ICTs in agricultural research, information is still constrained by the way it is published and the degree to which it is open. Piers Bocock of CGIAR shares how his organisation is addressing this.